2011
DOI: 10.1002/bem.20652
|View full text |Cite
|
Sign up to set email alerts
|

Review of possible modulation‐dependent biological effects of radiofrequency fields

Abstract: The biological effects of modulated radiofrequency (RF) electromagnetic fields have been a subject of debate since early publications more than 30 years ago, suggesting that relatively weak amplitude-modulated RF electromagnetic fields have specific biological effects different from the well-known thermal effects of RF energy. This discussion has been recently activated by the increasing human exposure to RF fields from wireless communication systems. Modulation is used in all wireless communication systems to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 103 publications
(114 reference statements)
2
44
2
Order By: Relevance
“…The difference between Tg and NT mice is brain production and aggregation/deposition of Aβ in Tg mice. Earlier studies have provided evidence that EMF treatment increases neuronal activity [16], [19], [21], [33], [34]. As mentioned previously, our very recent findings show that long-term EMF treatment does indeed increase neuronal activity in Tg and NT mice, irrespective of genotype [20].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The difference between Tg and NT mice is brain production and aggregation/deposition of Aβ in Tg mice. Earlier studies have provided evidence that EMF treatment increases neuronal activity [16], [19], [21], [33], [34]. As mentioned previously, our very recent findings show that long-term EMF treatment does indeed increase neuronal activity in Tg and NT mice, irrespective of genotype [20].…”
Section: Discussionsupporting
confidence: 85%
“…The fact that our long-term EMF treatment involves pulsed, modulated GSM signal is important because a recent, comprehensive review concluded that EMF-induction of biologic effects occurs primarily with GSM-type modulation and a pulsed signal - not continuous wave or UMTS fields [21].…”
Section: Introductionmentioning
confidence: 99%
“…According to (3), I Ca directly depends on the membrane potential. One possible way of controlling [Ca 2+ ] i is through change in membrane voltage V m , since it also drives the [Ca 2+ ] i according to (2).…”
Section: Relation Between Intracellular Calcium Concentration Andmentioning
confidence: 99%
“…In terms of non-invasive methods, recent studies performed showed that electromagnetic radiation (EMR) exposure and magnetic fields (MF) can improve the cognitive abilities of the brain eliminating the possibility that the positive effects were caused by increased temperature [1]- [3]. In terms of invasive methods, an ideal futuristic approach is to develop nano-machines based on graphene or carbon nanotubes, that can deliver drugs, mimic neurotransmitters, or expose neurons to EMR/MF at very specific targets, minimizing risk of side effects [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…External periodic electromagnetic stressor is expected to induce alterations in the brain bioelectric rhythms and EEG signal. Effects of the radio frequency electromagnetic field on human brain physiology have become of major interest with increasing applications of telecommunication devices [8][9][10]. Telecommunication devices employ radiofrequency radiation, modulated at different low frequencies.…”
Section: Introductionmentioning
confidence: 99%